2022
DOI: 10.3389/fspor.2022.1024996
|View full text |Cite
|
Sign up to set email alerts
|

Nudging digital physical activity breaks for home studying of university students—A randomized controlled trial during the COVID-19 pandemic with daily activity measures

Abstract: University students are of particular public health interest because they are at high risk for physical inactivity and sedentary behaviors. In conjunction with the COVID-19 pandemic, sedentariness and physical inactivity were reinforced, as the pandemic led to an increase in home studying. Physical activity (PA) breaks have been identified as promoting factors for university students' physical and mental health. Therefore, the present study explored an approach to nudge students to take PA breaks at home while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Of the 11 RCTs meeting the inclusion criteria and included in the systematic review, 8 (73%) [17][18][19][22][23][24][25][26] showed strongly positive results even considering that they referred to different age groups, from children to older adults, and to people from different countries and performed different modalities of coaching programs. Only three studies [20,21,27] showed no benefit or some benefit that was not completely effective. First, Ferreira et al [20] reported that the intervention in adolescents consisting of sending educational information on physical activities according to the Brazilian guidelines using illustrated messages through WhatsApp was not effective in increasing physical activity and reducing the time spent on sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 RCTs meeting the inclusion criteria and included in the systematic review, 8 (73%) [17][18][19][22][23][24][25][26] showed strongly positive results even considering that they referred to different age groups, from children to older adults, and to people from different countries and performed different modalities of coaching programs. Only three studies [20,21,27] showed no benefit or some benefit that was not completely effective. First, Ferreira et al [20] reported that the intervention in adolescents consisting of sending educational information on physical activities according to the Brazilian guidelines using illustrated messages through WhatsApp was not effective in increasing physical activity and reducing the time spent on sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Teuber et al using nudges sent via Microsoft Teams to 57 young students did not show any significant effect on their likelihood to participate in physical activity breaks on a given day. Instead, an individual-level effect revealed that the longer a student studied at home over the course of a day, the more likely they were to take a physical activity break [27].…”
Section: Main Findingsmentioning
confidence: 99%
“…Thus, the university sports department of the University of Tübingen launched various online sports courses and the student health management introduced an opportunity for a new digital form of PA breaks. This opportunity provided PA breaks via videos with guided physical exercises and health-promoting explanations for a PA break for everyday home studying: the so called "Bewegungssnack digital" [in English "exercise snack digital" (ESD)] [49]. The ESD videos took 5-7 min and were categorized into three thematic foci: activation, relaxation, and coordination.…”
Section: Study Settingmentioning
confidence: 99%
“…Participants were recruited within the framework of an intervention study, which was conducted to investigate whether a digital nudging intervention has a beneficial effect on taking PA breaks during home study periods [49]. Students at the University of Tübingen which counts 27,532 enrolled students were approached for participation through a variety of digital means: via an email sent to those who registered for ESD course on the homepage of the university sports department and to all students via the university email distribution list; via advertisement on social media of the university sports department (Facebook, Instagram, YouTube, homepage).…”
Section: Participantsmentioning
confidence: 99%
“…Societal polarization [ 237 , 238 ] has to be avoided and de-escalation should be prioritized [ 239 ]. This can be achieved with adequate communication [ 240 ] and not in paternalistic messages [ 241 ] that might even induce opposite effects [ 242 ].…”
Section: Reviewmentioning
confidence: 99%